Risk factors for venous thromboembolism after hip arthroscopy: a systematic review and meta-analysis - Haoxuan Li; Huan Zhang; Shengjie Zhou; Chaowei Hu; Yiyuan Guan; Ri Jin (Journal of Orthopaedic Surgery and Research)
Abstract Background Postoperative venous thromboembolism (VTE) following hip arthroscopy is associated with increased hospital readmissions and significant medical costs. However, the risk factors for postoperative VTE after hip arthroscopy remain a topic of debate. In this study, we aimed to quantitatively and comprehensively identify risk factors for postoperative VTE after hip arthroscopy, providing evidence for the development of clinical prevention strategies. Methods A systematic search was conducted using PubMed, Embase, Web of Science, Scopus, and the Cochrane Library databases from their inception to December 10, 2024. The search was limited to English-language articles that evaluated risk factors for postoperative VTE after hip arthroscopy. The quality of the included studies was assessed using the Newcastle–Ottawa Scale. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to assess the relationship between various risk factors and the incidence of postoperative VTE after hip arthroscopy. This protocol was registered with PROSPERO (registration number: CRD42024601636). Results Five studies, encompassing 71,815 patients who underwent hip arthroscopy, were included in the meta-analysis. The analysis identified obesity (OR: 1.41, 95% CI: 1.23–1.61), smoking (OR: 1.23, 95% CI: 1.04–1.45), and age > 45 years (OR: 1.49, 95% CI: 1.03–2.15) as significant risk factors for postoperative VTE. Conclusion Obesity, smoking, and age > 45 years are found to be significant risk factors for postoperative VTE after hip arthroscopy.